Inhaled budesonide does not affect hypoxic pulmonary vasoconstriction at 4559 meters of altitude - Berger, Marc Moritz; Fried, Sebastian; Bärtsch, Peter; Mairbäurl, Heimo (High altitude medicine & biology, 2018)
Inhaled budesonide does not affect hypoxic pulmonary vasoconstriction at 4559 meters of altitude. High Alt Med Biol 19:52–59, 2018.—Oral intake of the corticosteroid dexamethasone has been shown to lower pulmonary artery pressure (PAP) and to prevent high-altitude pulmonary edema. This study tested whether inhalation of the corticosteroid budesonide attenuates PAP and right ventricular (RV) function after rapid ascent to 4559 m. In this prospective, randomized, double-blind, and placebo-controlled trial, 50 subjects were randomized into three groups to receive budesonide at 200 or 800 μg twice/day (n = 16 and 17, respectively) or placebo (n = 17). Inhalation was started 1 day before ascending from 1130 to 4559 m within 20 hours. Systolic PAP (SPAP) and RV function were assessed by transthoracic echocardiography at low altitude (423 m) and after 7, 20, 32, and 44 hours at 4559 m. Ascent to high altitude increased SPAP about 1.7-fold (p < 0.001), whereas RV function was preserved. There was no difference in SPAP and RV function between groups at low and high altitude (all p values >0.10). Capillary partial pressure of oxygen (PO2) and carbon dioxide as well as the alveolar to arterial PO2 difference were decreased at high altitude but not affected by budesonide. Prophylactic inhalation of budesonide does not attenuate high-altitude-induced pulmonary vasoconstriction and RV function after rapid ascent to 4559 m.
Gesehen am 17.06.2019